Salidroside alleviates cachexia symptoms in mouse models of cancer cachexia via activating mTOR signalling. Issue 2 (18th January 2016) - Chen, Xiangzheng; Wu, Yangping; Yang, Tinghan; Wei, Mingtian; Wang, Yuxi; Deng, Xiangbing; Shen, Congcong; Li, Wenting; Zhang, Hang; Xu, Weiyong; Gou, Lantu; Zeng, Yong; et al.
Abstract: Background: Cachexia has a devastating impact on survival and quality of life for many cancer patients and contributes to nearly one‐third of all cancer deaths; also, it is associated with poor responses to chemotherapy and survival. A better understanding of the underlying mechanisms of cancer‐associated cachexia (CAC), coupled with effective therapeutic approaches, will improve management of progressive functional impairment in cancer patients. Salidroside, a phenylpropanoid glycoside in Rhodiola rosea L, has been reported to possess potential anti‐fatigue, anti‐ageing, and anti‐Alzheimer's disease properties. It is widely consumed as a nutritional supplement, but its effects on CAC and the possible mechanism remain a mystery. Methods: In the murine models of cachexia induced by CT‐26 and Lewis lung carcinoma (LLC) tumour, respectively, main features of CAC were determined after treatment of salidroside or chemotherapy. In vitro experiments were performed using murine C2 C12 myotubes, which were treated by tumour necrosis factor‐α. Levels of several critical muscle‐related signal proteins such as mammalian target of rapamycin (mTOR), p‐mTOR, and myosin heavy chain (MyHC) were examined using western blot both in vitro and in vivo . Results: In the present study, we showed the exciting effect of salidroside on the treatment of CAC. In CT‐26 and LLC models, respectively, salidroside treatment could effectively preserve the tumour‐free body weight, decrease loss of adipose and gastrocnemius muscles, alleviate tumour burden, and prolong their survival time. Additionally, in combined chemotherapy, salidroside could synergistically enhance the anti‐tumour activity of cisplatin, especially decreased or eliminated chemotherapy‐induced cachexia. Further analysis demonstrated that salidroside could significantly increase expression of mTOR, p‐mTOR, and MyHC in gastrocnemius muscle. Also, results in vitro showed that salidroside could not only obviously increase mTOR, p‐mTOR, and MyHC expression in C2 C12 myotubes but also effectively rescue their down‐regulation induced by tumour necrosis factor‐α. Conclusions: In the current study, the exciting effect of salidroside on CAC suggested that salidroside supplementation might be a promising approach for a multi‐targeted therapy for the treatment of CAC.